Exploring Employee Motivation: A Comprehensive Analysis of Key Motivational Factors Across Diverse Industries - Roslinda, Jay A.; Andias, Amiel B. (Future Science / FSH-PH Publications, 2025)
Motivated employees tend to be more productive, engaged, and are less likely to exhibit negative attitudes toward customers and colleagues, contributing significantly to overall organizational performance. This study employs a descriptive-quantitative research design to comprehensively examine key motivational factors influencing behavior and satisfaction across eight major industries: education, energy, finance and economics, food and beverage, health care, hospitality, pharmaceutical, and transportation. Data were gathered from a diverse sample of 353 respondents using a structured survey instrument designed to evaluate a multiple motivational drivers. These include good wages, appreciation for work done, job security, promotion and growth in the organization, interesting work, good working conditions, feeling of being in on things, tactful discipline, personal loyalty to employees, and sympathetic understanding of, or help with others. The analysis revealed that “good wages” consistently emerged as the most influential motivational factor across all sectors, emphasizing the fundamental importance of competitive financial compensation in enhancing employee motivation, engagement, and retention. In contrast, “sympathetic understanding of, or help with others” ranked as the least impactful factor, indicating that while emotional support is valued, it is generally less effective than tangible rewards in motivating employees to perform at high levels. These findings offer critical insights for organizational leaders and human resource professionals, highlighting the need to balance financial and non-financial motivators. Developing well-rounded, evidence-based motivational strategies that align with employee expectations and industry-specific needs can lead to higher employee satisfaction, reduced turnover, and improved organizational performance.